Salt Productivity Investigation from the Human Resources Aspect - Eni puji Estuti; Wachidah Fauziyanti; Silvia Hendrayanti (MediaTrend, 2022)
The territory of Indonesia is a country that has the fourth longest coastline in the world. This vast sea should be able to produce salt abundantly. This natural resource has not been processed optimally so that until now salt has become an imported commodity. This problem has not been able to find the right solution so that Indonesia does not need to import salt. Man's role is a very decisive thing in every production activity that he does. This research will explain salt productivity in terms of human resources. This research method is quantitative research, data analysis using multiple regression analysis. Age and skill have a positive and significant effect on the productivity of salt farmers. Experience has a negative and significant effect on the productivity of salt farmers. Age is related to the energy possessed to work on salt fields, to be able to increase salt production it takes strong energy and physical strength. Skills are needed in making technical steps about environmental situations and weather changes that occur. so with a strong physique and good skills it is expected that salt productivity will increase.